Evaluation of 2, 6-dichlorophenolindophenol acetate as a substrate for acetylcholinesterase activity assay. (October 2015) - Pohanka, Miroslav; Holas, Ondrej
Abstract Ellman's method is a standard protocol for the determination of cholinesterases activity. Though the method is ready for laboratory purposes, it has some drawbacks as well. In the current article, 2, 6-dichloroindophenol acetate is performed as a chromogenic substrate suitable for acetylcholinesterase (AChE) activity examination. Michaelis constant and maximal velocity for 2, 6-dichloroindophenol acetate were determined (38.0 µM and 244 pkat) and compared to the values for acetythiocholine (Km 0.18 mM; Vmax 5.1 nkat). Docking for 2, 6-dichloroindophenol acetate and human AChE was done as well. In conclusion, 2, 6-dichloroindophenol acetate seems to be suitable chromogenic substrate for AChE and spectrophotometry and based on this it can be easily performed whenever AChE activity should be tested.